Cryopreservation of in vitro grown shoot tips and apical meristems of the forage legume Arachis pintoi - Rey de Badaró, Hebe Yolanda (2009)
A cryopreservation protocol using the encapsulation-dehydration procedure was established for shoot tips (2-3 mm in length) and meristems (0.3-0.5 mm) sampled from in vitro plantlets of diploid and triploid cytotypes of Arachis pintoi. The optimal protocol was the following: after dissection, explants were precultured for 24 h on establishment medium (EM), encapsulated in calcium alginate beads and pretreated in liquid EM medium with daily increasing sucrose concentration (0.5, 0.75, 1.0 M) and desiccated to 22-23% moisture content (fresh weight basis). Explants were frozen using slow cooling (1ºC min-1 from 25ºC to -30ºC followed by direct immersion in liquid nitrogen), thawed rapidly and post-cultured in liquid EM medium enriched with daily decreasing sucrose concentrations (0.75, 0.50, 0.1 M). Explants were then transferred to solid EM medium in order to achieve shoot regeneration, then on Murashige and Skoog medium supplemented with 0.05 μM naphthalene acetic acid to induce rooting of shoots. With this procedure, 53% and 56% of cryopreserved shoot tips of the diploid and triploid cytotypes, respectively, survived and formed plants. However, Orly 16% of cryopreserved meristems of both cytotypes regenerated plants. Using ten isozyme systems and seven RAPD profiles, no modification induced by cryopreservation could be detected in plantlets regenerated from cryopreserved material.